Mimicking Bacterial Learning and Memory in Tungsten Based Two-Sided Single Layers of WSeO, WSeS, WSeSe, and WSeTe - Turfanda, Aykut; Ünlü, Hilmi (AIP Publishing, 2023)
We mimic bacterial learning and memory abilities in tungsten based two-sided single layers of WSeO, WSeS, WSeSe, and WSeTe, where the thickness of the material represents the growth in time. We aim to create a quantum memristor like system to show learning and memory abilities of bacteria with time while it grows. Its governing equation is derived, and it was found to be similar to the gene regulatory response model of the bacteria. Polarization is calculated from the Berry phase theory to plot its relation with the degauss parameter in time, which leads to bow-tie like memory switches similar to phase-change memories. We attribute this behavior to a specific bacteria, that is, Geobacter metallireducens. Mimicking bacteria’s learning and memory abilities will open a way to merge physical intelligence with quantum computing computationally.